3D MHD models of the centrifugal magnetosphere from a massive star with an oblique dipole field. Issue 3 (1st February 2023) - ud-Doula, Asif; Owocki, Stanley P; Russell, Christopher; Gagné, Marc; Daley-Yates, Simon
ABSTRACT: We present results from new self-consistent 3D magnetohydrodynamics (MHD) simulations of the magnetospheres from massive stars with a dipole magnetic axis that has a non-zero obliquity angle (β) to the star's rotation axis. As an initial direct application, we compare the global structure of co-rotating discs for nearly aligned (β = 5°) versus half-oblique (β = 45°) models, both with moderately rapid rotation (∼0.5 critical). We find that accumulation surfaces broadly resemble the forms predicted by the analytical rigidly rotating magnetosphere model, but the mass buildup to near the critical level for centrifugal breakout against magnetic confinement distorts the field from the imposed initial dipole. This leads to an associated warping of the accumulation surface towards the rotational equator, with the highest density concentrated in wings centred on the intersection between the magnetic and rotational equators. These MHD models can be used to synthesize rotational modulation of photometric absorption and H α emission for a direct comparison with observations.